Perancangan Sistem Informasi Hasil Produksi Sawit pada PT. Torganda Berbasis Web - Butarbutar, Cecilia Margareta; Resianta Parangin-angin; Rijois Iboy E. Saragih (Universitas Methodist Indonesia, 2025)
The palm oil industry is one of the strategic sectors in the Indonesian economy, but the management of its production data still faces several obstacles, especially in recording and reporting processes that are still carried out manually. This study aims to design and develop a web-based information system for palm oil production at PT. Torganda to improve efficiency, accuracy, and data processing speed. The research methods used include observation, documentation, and system analysis. The system was designed using Data Flow Diagrams (DFD), Entity Relationship Diagrams (ERD), and a structured database design. The results indicate that the system can automate harvest data processing, accelerate the creation of daily, monthly, and annual reports, and provide real-time information access. Thus, the system has the potential to improve operational performance and support timely decision-making at PT. Torganda.